Autonomous nervous system modulation in supine and standing postures in children with probable developmental coordination disorder. Issue 1 (January 2021) - Gama, Daniel T.; Ferracioli-Gama, Marcela C.; Barela, José A.; Takahashi, Anielle C.M.; Pellegrini, Ana Maria; Hiraga, Cynthia Y.
Abstract: Background: Children with Developmental Coordination Disorder (DCD) are known to have poor physical fitness and psychosocial problems. The autonomous nervous system (ANS) plays an essential role in the regulation of human neurophysiological processes. Inadequate ANS modulation has been associated with harmful health conditions such as poor aerobic power, high body mass index, and symptoms of stress and anxiety. Modulation of ANS in children with DCD needs to be further investigated taking into consideration variables that may influence its function. For instance, would the level of physical fitness or the symptoms of stress and anxiety affect the ANS modulation of children with DCD? Aims: To examine the ANS modulation during supine and standing postures, and stress/anxiety with questionnaire data from children with probable-DCD (p-DCD). Methods: and procedures: Thirty children, 8–12 years old, composed two groups paired by age, gender, peak volume of oxygen uptake (aerobic power), and body mass index (BMI): p-DCD (9 boys, mean age 10.8 y) and typically developing (TD). Both groups were compared for stress/anxiety assessment by questionnaire and spectral, symbolic, and complexity heart rate variability (HRV) analyses during posture changes. Outcomes and results: p-DCD group showed higher stress symptoms than TD group for stress/anxiety assessment in the questionnaire's data, but HRV analyses showed no differences between the two groups. Both groups showed parasympathetic prevalence during supine posture and sympathetic prevalence during standing posture. Conclusions and implications: Children with p-DCD had similar autonomic control function as TD children during posture change (supine to standing). Symptoms of stress and anxiety demonstrated by p-DCD did not impact their ANS modulation. These results indicate that aerobic power and BMI are probable protective factors of ANS modulation for these children. Abstract : Developmental coordination disorder (DCD); Autonomous nervous system; Heart rate variability; Stress and anxiety.